Debris Index of Children With Brushing Their Teeth 1, 2, And 3 Methods in Elementary School 26 Surau Labuah Agam District - Zulfikri zulfikri; Reni Rahmanita (Jurnal Kesehatan Masyarakat Andalas, 2017)
Brushing Teeth is one of the efforts in maintaining oral hygiene, one of which is cleaning debris (food waste) that stickto the teeth and to keep the teeth clean and healthy. This study aims to find out the debris index image between brushing teeth with 1 method, 2 methods and 3 methods in children aged 10-12 years. The study design was descriptive approach with cross sectional study. The research sample of 70 people consisting of 28 men and 42 women. The sampling technique used  totalsampling. Data analysis of  univariate analysis. The results showed that children with the brushing teeth using 1 method most of debris index withlow or bad criteria  as much as 83.33%, children with the brushing teeth using 2 methods most of debris index low or badcriteria  as much as 54.84% and children with the brushing teeth using  3 methods most of debris index with middle criteria as much as 75.76%. It is suggested to the children to brush their teeth with the correct technique so that the dental and oral hygiene is improved and maintained